2019
DOI: 10.1167/19.5.15
|View full text |Cite
|
Sign up to set email alerts
|

The contributions of central and peripheral vision to scene-gist recognition with a 180° visual field

Abstract: We investigated the relative contributions of central versus peripheral vision in scene-gist recognition with panoramic 1808 scenes. Experiment 1 used the window/scotoma paradigm of Larson and Loschky (2009). We replicated their findings that peripheral vision was more important for rapid scene categorization, while central vision was more efficient, but those effects were greatly magnified. For example, in comparing our critical radius (which produced equivalent performance with mutually exclusive central and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 90 publications
0
23
3
Order By: Relevance
“…As a result visual information quality drops as a function of the eccentricity to the fovea [ 8 , 9 ]. Despite its limitations, peripheral vision helps build a global representation of scenes [ 10 , 11 ]. The work of Boucart et al [ 11 , 12 , 13 ] served to demonstrate that scene categorization stays above chance-level even at high visual eccentricities (70 deg.…”
Section: Introductionmentioning
confidence: 99%
“…As a result visual information quality drops as a function of the eccentricity to the fovea [ 8 , 9 ]. Despite its limitations, peripheral vision helps build a global representation of scenes [ 10 , 11 ]. The work of Boucart et al [ 11 , 12 , 13 ] served to demonstrate that scene categorization stays above chance-level even at high visual eccentricities (70 deg.…”
Section: Introductionmentioning
confidence: 99%
“…However, Laubrock et al (, p. 249) point out that comic readers can likely recognize the gist of the background within their first fixation of a comic panel using their peripheral vision (i.e., without fixating it). Specifically, studies have shown that, within a single fixation on a photograph, viewers can accurately categorize the scene background (e.g., beach vs. mountain vs. street vs. bedroom) using only their peripheral vision (Boucart, Moroni, Thibaut, Szaffarczyk, & Greene, ; Larson & Loschky, ; Loschky, Szaffarczyk, Beugnet, Young, & Boucart, ). Thus, it is currently unclear whether the category of a background or of a character is processed earlier while viewing visual narratives.…”
mentioning
confidence: 99%
“…Several studies have highlighted the importance of peripheral vision during the categorization of scenes (Trouilloud et al, 2020;Loschky, Szaffarczyk, Beugnet, Young, & Boucart, 2019;Lukavsky, 2019;Geuzebroek & van den Berg, 2018;Boucart, Moroni, Thibaut, Szaffarczyk, & Greene, 2013;Larson & Loschky, 2009). The categorization of scenes remains possible even in far peripheral vision (70°retinal eccentricity; Boucart et al, 2013).…”
Section: Peripheral Vision Influence and Physical Similarity Effectmentioning
confidence: 99%